2020
DOI: 10.1021/acsinfecdis.0c00259
|View full text |Cite
|
Sign up to set email alerts
|

Screening an Established Natural Product Library Identifies Secondary Metabolites That Potentiate Conventional Antibiotics

Abstract: Health organizations worldwide have warned that we are on the cusp of a "post-antibiotic era," necessitating new approaches to combat antibiotic resistant infections. One such approach is the development of antibiotic adjuvants, which have little or no inherent antibiotic activity at their active concentrations but instead potentiate the activity of antibiotics against antibiotic-resistant bacteria. Recently, we demonstrated that meridianin D, a natural product originally reported to have activity against Stap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…Finally, given that it has been reported that polymyxin antibiotics induce cell death by generating reactive oxygen species (ROS), , we examined the effect of lead benzimidazole adjuvants on ROS generation using 2′,7′-dichlorofluorescin diacetate (DCFH-DA) as previously reported (Figure ). Compared to untreated cells, ROS levels in both AB4106 and KPB9 increased upon treatment with active compounds, by between 78% and 934%, with the exception of compound 20 , for which ROS generation was decreased to 64% for AB4106 and 51% for KPB9.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, given that it has been reported that polymyxin antibiotics induce cell death by generating reactive oxygen species (ROS), , we examined the effect of lead benzimidazole adjuvants on ROS generation using 2′,7′-dichlorofluorescin diacetate (DCFH-DA) as previously reported (Figure ). Compared to untreated cells, ROS levels in both AB4106 and KPB9 increased upon treatment with active compounds, by between 78% and 934%, with the exception of compound 20 , for which ROS generation was decreased to 64% for AB4106 and 51% for KPB9.…”
Section: Resultsmentioning
confidence: 99%
“…In the context of colistin resistance, we and others have identified a number of adjuvants that suppress resistance in bacterial strains that harbor either chromosomally or plasmid encoded resistance determinants. These include the 2-aminoimidzole 1 , the tryptamine derivative 2 , the meridianin D analogue 3 , salicylanilides IMD-0354 4 , niclosamide 5 , the natural products kuwanon G 6 , prodigiosin 7 , the antifungal drug econazole 8 (Figure ), and others. …”
mentioning
confidence: 99%
“…[11] In an effort to increase the number of scaffolds for adjuvant development, we recently evaluated the natural products contained within the National Cancer Institute's (NCI's) Natural Product Library Set IV for resistance breaking activity across multiple antibiotic classes and bacterial species. [12] One of the most effective adjuvants identified for breaking colistin resistance was prodigiosin (Figure 1), a tripyrrolic natural product produced by Serratia marcescens. [13] We discovered that prodigiosin reduced the minimum inhibitory concentration (MIC) of colistin in a highly colistin resistant strain, A. baumannii AB4106, from 1024 μg/mL to 4 μg/mL at a concentration of 5 μM.…”
Section: Introductionmentioning
confidence: 99%
“…[13] We discovered that prodigiosin reduced the minimum inhibitory concentration (MIC) of colistin in a highly colistin resistant strain, A. baumannii AB4106, from 1024 μg/mL to 4 μg/mL at a concentration of 5 μM. Against K. pneumoniae strain B9, prodigiosin lowered the colistin MIC from 512 μg/mL to 2 μg/mL at a concentration of 1.25 μM, [12] with this latter result being especially noteworthy since an MIC of 2 μg/mL is the susceptibility/intermediate breakpoint of colistin in this species. [14] We further demonstrated that the synthetic BCL-2 inhibitor obatoclax [15] (Figure 1), a compound similar in structure to prodigiosin, was also an effective colistin adjuvant.…”
Section: Introductionmentioning
confidence: 99%
“…Multidrug resistance is a major global public health issue caused due to the indiscriminate use of broad-spectrum antimicrobial and also the usage of counterfeit antimicrobials (1). Such falsified and substandard antimicrobials may contain toxic doses of dangerous ingredients, compromise the treatment of chronic and infectious diseases, causing disease progression, drug resistance, and increases the mortality rate (2).…”
Section: Introductionmentioning
confidence: 99%